THE DIALECTICAL RELATIONSHIP BETWEEN ELEMENTS IN THE VIETNAM POLITICAL SYSTEM - Associate Professor Dr. Huynh Thi Gam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The political system of a country represents the views, ways, and ideas of that country. Each country has different ideological characteristics than the political system does not express the thoughts of one person, of an organization but is made up of many political organizations, working together for the same way and the point of view of that country. So how is the relationship between the parts that make up the Vietnamese political system? How are the position, role, and functions of the parts constituting the Vietnamese political system? This study focuses on analysing the problems posed in the questions above; at the same time point out the distinctive features of the Vietnamese political system.